How do reputation risks affect powerful taxp(l)ayers\' behavior? - Santos, Rogiene Batista dos (2020)
This study investigates the practices of tax avoidance of financial institutions. There are two main motivations for this study: one theoretical and other empirical. The first relates to theoretical modeling based on game theory to analyze tax avoidance of banks. The second involves to the examination of the results of the theoretical model by, empirically, analyzing a database. This study is composed of two parts. The first part proposes a theoretical model based on game theory that considers the interplay of the IRS and two types of taxpayers: Complex and Simple (Banks and Non-banks, respectively). When considering that the reputation costs are similar for these two groups, we find that, at the equilibrium, Banks are more aggressive than Non-banks in practicing tax avoidance. However, when considering that Banks have higher reputation costs, we find that Non-banks are more aggressive. By performing comparative statics we find that Banks benefit when the fine increases. A solution is to increase the reputation cost and fine, simultaneously. The second part of this study, empirically, tests the first result of the theoretical model, showing that Banks are not so aggressive when practicing tax avoidance. For this purpose, we use a sample composed by U.S. public firms, covering the period 2000-2018, totaling 110,030 firm-years. The empirical results show no difference in the level of tax avoidance between financial companies and companies from other sectors. Economically, not having confirmed the research hypothesis that financial companies practice less tax avoidance than companies from other sectors implies that perhaps reputation costs have little effect on financial institutions\' tax avoidance practices. It is possible that the effect of reputation costs does not directly affect financial companies. Therefore, its effect would be marginal. This study provides evidence for a better understanding of tax avoidance and the reputation costs of this practice of financial institutions. The results obtained are relevant for academics and policymakers.